Capitalism and peasant agriculture in Africa - Nyong'o, Peter Anyang', 1945-
Paper prepared for the Mawazo workshop on the Agrarian question in d eveloping countries.
AR/MISR/96/6/1
English
Shelf no. 1.
Keywords: Peasantry -- Africa; Capitalism -- Africa; Agriculture -- Economic aspects